Evaluation of stability and safety of equine mesenchymal stem cells derived from amniotic fluid for clinical application - Kim, Eun Young; Lee, Eun Ji; Kim, Ryoung Eun; Kil, Tae Young; Kim, Min Kyu (Frontiers in Veterinary Science, 2024)
Amniotic fluid mesenchymal stem cells (AF-MSCs), which can be obtained from fetal tissue, reportedly have self-renewal capacity and multi-lineage differentiation potential. The aim of this study was to identify the biological characteristics of AF-MSCs and evaluate their stability and safety in long-term culture. To confirm the biological characteristics of AF-MSCs, morphology, proliferation capacity, karyotype, differentiation capacity, gene expression level, and immunophenotype were analyzed after isolating AF-MSCs from equine amniotic fluid. AF-MSCs were differentiated into adipocytes, chondrocytes, and osteocytes. Immunophenotype analyses revealed expression levels of ≥95% and ≤2% of cells for a positive and negative marker, respectively. Analysis of the MSCs relative gene expression levels of AF-MSCs was approximately at least twice that of the control. The endotoxin level was measured to verify the safety of AF-MSCs and was found to be less than the standard value of 0.5 EU/ml. AF-MSCs were cultured for a long time without any evidence of abnormalities in morphology, proliferation ability, and karyotype. These results suggest that amniotic fluid is a competent source for acquiring equine MSCs and that it is valuable as a cell therapy due to its high stability